The Effectiveness of BAZNAS Productive Zakat Programme in Poverty Alleviation: A CIBEST Model Approach - Nur Fitry Latief; Syamsul Alam (LP2M IAIN Palopo, 2026)
This study evaluates the effectiveness of the Badan Amil Zakat Nasional (BAZNAS) productive zakat programme in alleviating poverty among mustahiq recipients in Manado, North Sulawesi, Indonesia, using the Combined Islamic Poverty Index and Spiritual Index (CIBEST) model. The CIBEST model provides a multidimensional assessment integrating both material welfare food, clothing, housing, education, and health and spiritual welfare faith (aqidah), worship (ibadah), morality (akhlak), family harmony, and religious knowledge thereby reflecting Islamic economics principles of holistic human welfare. A pre-test/post-test quasi-experimental design was employed, collecting data from 248 mustahiq recipients across four programme types: productive capital loans, skill and vocational training, business mentoring, and digital marketing assistance. Instruments were validated and reliable (Cronbach's α > 0.70). Paired t-tests and McNemar's tests were applied to assess pre-post differences. Results demonstrate that the proportion of mustahiq in the Welfare Quadrant (Q1) increased significantly from 18.4% to 47.3% (Δ = +28.9 percentage points), while the Absolute Poverty Quadrant (Q4) declined from 36.2% to 13.2% (Δ = −23.0 pp). The CIBEST Welfare Index rose from 0.41 to 0.69 overall (Cohen's d = 0.77, large effect), with digital marketing assistance producing the largest gain (IW: 0.41 → 0.73). All changes were statistically significant (p < 0.001). Spiritual welfare scores also showed consistent improvement across all indicators, with modest but meaningful gains. The findings confirm that productive zakat, when structured around Big Data-informed targeting (Latief, 2025a) and strategic management principles (Latief, 2025b), can generate substantial and measurable poverty reduction outcomes. The CIBEST model is validated as an appropriate, culturally grounded, and empirically sensitive instrument for zakat effectiveness evaluation in Indonesia.